Academic Misconduct and Online Support for Students - Wong, Amara (Canadian Perspectives on Academic Integrity, 2021)
In response to the shift to fully online delivery of student services in March 2020, the University of the Fraser Valley’s Academic Success Centre quickly revamped the way we connect with and support students charged with academic misconduct. Our presentation will explain the historical and philosophical foundations of our Academic Integrity Matters (AIM) program including the training of our student Peer Mentors and the key role they have. We will describe the multi-step workshop process we developed to guide students to stronger understanding of academic misconduct, academic integrity, and their own role as models of academic honesty. We will present data showing how the pandemic impacted the number of misconduct cases and the types committed. We will conclude the workshop with an outline of the challenges we encountered and how we resolved them as we altered an already successful face-to-face program to run in a virtual environment. Participants will be invited to discuss how our approach might apply in their own contexts.